Prediction and prevention of late-onset pre-eclampsia: a systematic review - Baylis, Anna; Zhou, Wei; Menkhorst, Ellen; Dimitriadis, Evdokia (Frontiers in Medicine, 2024)
Background Pre-eclampsia is a major cause of perinatal morbidity and mortality worldwide. Late-onset pre-eclampsia (LOP), which results in delivery ≥34 weeks gestation, is the most common type. However, there is a lack of knowledge in its prediction and prevention. Improving our understanding in this area will allow us to have better surveillance of high-risk patients and thus improve clinical outcomes. Methods A systematic review was performed using a search of articles on PubMed. The search terms were ((late-onset) AND (pre-eclampsia)) AND ((risk factor) OR (risk) OR (prediction) OR (management) OR (prevention)). Primary literature published between 1 January 2013 and 31 December 2023 was included. Human studies assessing the prediction or prevention of late-onset pre-eclampsia were eligible for inclusion. Results Sixteen articles were included in the final review. The key risk factors identified were Body Mass Index (BMI), chronic hypertension, elevated mean arterial pressures (MAPs), nulliparity, and maternal age. No clinically useful predictive model for LOP was found. Initiating low dose aspirin before 17 weeks gestation in high-risk patients may help reduce the risk of LOP. Conclusion While aspirin is a promising preventor of LOP, preventative measures for women not deemed to be at high-risk or measures that can be implemented at a later gestation are required. Biomarkers for LOP need to be identified, and examining large cohorts during the second or third trimester may yield useful results, as this is when the pathogenesis is hypothesized to occur. Biomarkers that identify high-risk LOP patients may also help find preventative measures.